La morosidad y su incidencia en la recaudación del impuesto predial en la Municipalidad Distrital de Punchana periodo 2021 al 2023 - Valera Perez, Christian Paul (2025)
The study investigates the incidence of delinquency in the collection of property tax in the District Municipality of Punchana for the years 2021-2023. A total of 384 taxpayers were surveyed using a quantitative approach research, non experimental design and correlational scope to evaluate their tax culture and knowledge, as well as the success of the municipality's distribution plans used. The results revealed that poor tax culture, distrust in municipal management and low effectiveness of dissemination techniques influence non-payment; thus, delinquency negatively influences property tax collection. It is argued that the main ways to reduce delinquency and maximize municipal revenues are to improve tax education, expand transparency and update collection systems.